155. Infective Endocarditis and Cardiac Valve Surgery During the Opioid Epidemic in North Carolina, 2007 to 2017. (26th November 2018) - Schranz, Asher; Fleischauer, Aaron; Chu, Vivian H; Rosen, David
Abstract: Background: Infective endocarditis (IE) associated with drug use (DA-IE) is rising nationally. North Carolina (NC), a state hard-hit by the opioid epidemic, saw an over 12-fold increase in DA-IE from 2010 to 2015. Concerns about surgery exist due to the risk of ongoing drug use and reinfection after valvuloplasty. We evaluated trends, characteristics, and outcomes of valve surgery for DA-IE, compared with IE not associated with drug use (non-DA-IE), in NC. Methods: We analyzed the NC Discharge Database, which includes administrative data from all hospital discharges in NC. Using International Classification of Diseases codes, we identified all persons ≥18 years of age with IE from July 1, 2007 to June 30, 2017. Hospitalizations were deemed DA-IE by a diagnosis code related to illicit drug use, dependence, poisoning or withdrawal (excepting marijuana), or Hepatitis C in a person born after 1965. All others were labeled non-DA-IE. Procedure codes were queried to identify cardiac valve surgery. Year-to-year trends in surgery for IE by drug-associated status were reported. Demographics, length of stay (LOS), charges, and disposition were compared among DA-IE and non-DA-IE. Results: A total of 22, 809 hospitalizations were coded for IE. Valve surgery occurred in 1, 652. Of surgical hospitalizations, 17% overall and 42% in the final study year were DA-IE. Hospitalizations for DA-IE where surgery was done increased from <10 through 2012–2013 to 109 in 2016–2017 (figure). Compared with non-DA-IE, those undergoing surgery for DA-IE were younger (median age 33 vs. 56), female (47% vs. 33%), White (89% vs. 64%), uninsured (34% vs. 11%), insured by Medicaid (39% vs. 13%), and had tricuspid valve surgery (38% vs. 11%). DA-IE had longer median LOS (27 vs. 17 days) and were less often discharged home (51% vs. 59%). For the 287 DA-IE admissions with surgery, median hospital charges were $247, 524, totaling over $79, 000, 000. All comparisons were significant at P < 0.0001. Conclusion: From 2007 to 2017, valve surgeries for DA-IE in NC rose over tenfold and are approaching half of all surgeries for IE. This phenomenon is an underappreciated and morbid component of the opioid epidemic that burdens hospital and state resources. Research into best practices for managing patients with DA-IE and addressing addiction in this setting is critically needed. Disclosures: All authors: No reported disclosures.